2010
DOI: 10.1161/hypertensionaha.109.143024
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness Is Independently Associated With Rate of Renal Function Decline in Chronic Kidney Disease Stages 3 and 4

Abstract: Abstract-Aortic stiffness and chronic kidney disease are closely linked by shared risk factors and associated increased cardiovascular mortality. At lower levels of renal function, aortic stiffness is independently associated with glomerular filtration rate. However, the longitudinal impact of aortic stiffness on renal function has not been reported previously. A cohort of 133 patients with chronic kidney disease stages 3 and 4 (estimated glomerular filtration rate: 15 to 59 mL/min per 1.73 m 2 ) underwent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
166
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(186 citation statements)
references
References 40 publications
(37 reference statements)
10
166
2
8
Order By: Relevance
“…Previous studies on the association between arterial stiffness and decline in kidney function have been inconsistent (7,(9)(10)(11)(12)(13)(14)28). In a study including patients with CKD, Ford et al (9) showed that higher PWV but not pulse pressure was associated with the rate of change in kidney function.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies on the association between arterial stiffness and decline in kidney function have been inconsistent (7,(9)(10)(11)(12)(13)(14)28). In a study including patients with CKD, Ford et al (9) showed that higher PWV but not pulse pressure was associated with the rate of change in kidney function.…”
Section: Discussionmentioning
confidence: 98%
“…In a study including patients with CKD, Ford et al (9) showed that higher PWV but not pulse pressure was associated with the rate of change in kidney function. Similarly, in a Japanese cohort, an association was observed between higher brachial PWV and steeper decline in eGFR (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population and subjects with hypertension, the role of impedance gradient attenuation and the resulting microvascular changes were mainly observed in low-resistance circulations, such as kidney or brain. [6][7][8][9][10][11][12][13] In patients with ESRD, the microvascular disorders are generalized, involving muscular, cutaneous, renal, and myocardial circulations. [37][38][39][40] Decreased postocclusion or thermal muscular and cutaneous hyperemia was observed in patients with ESRD and associated with cardiovascular risk and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 The central effect of aortic stiffness on impedance gradient attenuation and resulting excessive transfer of pressure and pulsatile flow into microvasculature is mainly observed in low-resistance circulations: the kidney or brain. [6][7][8][9] The associations between increased aortic PWV and decreased renal function 10 or extent of brain white matter leukoaraiosis are well described. 8,[11][12][13] Impedance gradient is dependent on wall properties together with the structural gradient and taper from thoracic to abdominal aorta.…”
mentioning
confidence: 99%